Is Morning Exposure Therapy More Successful? Pilot Data on Exposure Process Indicators and Diurnal Cortisol in Obsessive–Compulsive Disorder or Agoraphobia - Michael Kellner; Maja Santai Mareljic; Alexander Yassouridis (Journal of Clinical Medicine, 2026)
Background/Objectives: Glucocorticoids have been shown to improve fear extinction learning in preclinical and human studies. We hypothesized an impact of the circadian rhythm of cortisol on exposure therapy in patients with anxiety spectrum disorders. Methods: Sixteen patients suffering from obsessive–compulsive disorder and eight with agoraphobia participated in a pilot randomized prospective cohort study. During two therapist-guided sessions of exposure therapy with response prevention, both starting either at 08:00 (morning group) or at 16:00 (late afternoon group), subjective units of distress (SUD) and salivary cortisol levels were assessed repeatedly. Results: While expected significant diurnal differences in salivary cortisol emerged between daytime groups, after controlling for chronotype, no significant differences were detected in our exposure process indicators of within-session and between-session habituation and distress-related expectancy violation towards maximal SUD and SUD at end. Nearly one-hundred subjects in each group would be needed to gain statistically significant daytime differences for these indicators as per case number estimation. Conclusions: Our preliminary results from this transdiagnostic sample do not provide support for scheduling exposure sessions in the morning. Further research should consider cortisol administration before exposure sessions to test whether different doses of exogenous glucocorticoids can augment exposure therapy outcomes.